Energetika dogajanj v ozračju - Rakovec, Jože (Obzornik za matematiko in fiziko, 2008)
In the paper is explained, with the help of the energy equations, which are the energy transforms that govern the weather processes: from the differential heating/cooling by the solar irradiance and the infrared terrestrial radiant exitance trough the available potential energy into the kinetic energy of the atmosphere, and from it by the viscous friction into the internal energy.
Keywords: energija; meteorologija; ozračje